Modelagem numérica de fluxo no sistema aquífero cristalino, município de Itu (SP) - Navarro, Juan [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The crystalline aquifer system occurs in the eastern portion of São Paulo state, with 61,312 km2 area. Due to the low productivity associated to this aquifer, it is still few used as a water resource, a scenario that has changing with the growing cities demand. Previous studies has associated higher productivity to the existence of expressive lineaments, a thick weathered zone, or the presence of few expressive fractures connected to water bodies. With the objective of understanding the groundwater governing dynamics in crystalline terrains, focusing on surface water contribution in deep tubular wells production, the present study developed a numerical flow model based on information gathered from field lithostructural survey, interpretation of pumping test diagnostic plot and stable isotopes analysis. The finite elements method was used to elaborate the model through FEFLOW algorithm. The structural survey shows predominance of two main fracture families, both vertical and high frequency; the vertical fracture analytical model was fitted to drawdown and derivative plots; the isotopic data suggest surface water contribution in deep tubular well production located next to water body. The conceptual model elaborated admits a set of hidraulically interconnected subvertical discontinuities, responsible for connecting the pumping well to the river. Based on the numerical simulation results, the maximum contribution of surface water in the well production after 1440 minutes of continuous pumping was estimated at 12.6%, while the aquifer would account for 87.3% of the volume extracted

O sistema aquífero cristalino ocorre na porção leste do estado de São Paulo, com 61.312 km2 de área. Devido à baixa produtividade associada a este aquífero, ainda é pouco utilizado como recurso hídrico, cenário que tem se alterado frente à crescente demanda dos municípios. Estudos anteriores associam maiores produtividades à existência de lineamentos expressivos, manto de alteração espesso ou à presença de fraturas de pouca expressão conectadas a corpos d'água. Com o objetivo de compreender a dinâmica governante do fluxo subterrâneo em terrenos cristalinos, tendo enfoque na contribuição de corpos d'água superficiais na produção de poços tubulares profundos, o presente estudo confeccionou modelo numérico de fluxo com base em informações reunidas a partir de levantamento litoestrutural de campo, interpretação de curva diagnóstica de teste de bombeamento e análise de isótopos estáveis. O método utilizado para elaboração do modelo numérico foi o dos elementos finitos, através do algoritmo FEFLOW. O levantamento das estruturas aponta predominância de duas famílias principais de fraturas, ambas subverticais e com alta frequência; o modelo analítico ajustado para as curvas de rebaixamento e derivativa foi o de fratura vertical; e os dados isotópicos sugerem a contribuição de águas superficiais na produção de poço tubular profundo situado próximo a corpo d'água. O modelo conceitual elaborado admite um conjunto de descontinuidades subverticais interconectadas hidraulicamente e responsáveis por conectar o poço de bombeamento ao rio. Com base nos resultados da simulação numérica, a contribuição máxima de água superficial na produção do poço, após 1440 minutos de bombeamento contínuo, foi estimada em 12,6%, enquanto o aquífero seria responsável por 87,3% do volume extraído
Keywords: Hidrogeologia; Aquiferos; Bombeamento de água; Itu (SP)